Pengaruh Kepemimpinan Demokrasi, Keadilan Organisasi dan Kepuasan Kerja Terhadap Komitmen Organisasi Di Cafe Basa-Basi Yogyakarta - Muhammad Arif Abdillah; Prayekti Prayekti; Jajuk Herawati (Universitas Batanghari Jambi, 2023)
The research objective was to determine the influence of democratic leadership, organizational justice, and job satisfaction on the organizational commitment of Basa-Basi CafÃ© Yogyakarta. This research is a quantitative research. The research population is all employees of Cafe Basa-Basi Yogyakarta, totaling 50 employees. The research sample is the entire population, amounting to 50 employees of Cafe Basa-Basi Yogyakarta. The technique of determining the sample using gross sampling technique. Data collection techniques using a questionnaire. Data analysis techniques used descriptive statistical analysis, and classical hypothesis testing included testing for normality, multicollinearity and heteroscedasticity, as well as multiple regression testing. The results showed that democratic leadership, organizational justice, and job satisfaction had a partial and simultaneous positive and significant effect on employee organizational commitment at CafÃ© Basa-Basi Yogyakarta.